(3efJbi MOjK CHj YHO Gddg eMeO Hf eNdO Hf MaUd GdYWGQ GdOhQis - (3YHO GdhGMO Hf eMeO Hf YHO Gddg Hf egOj GdaGQSjs
(3ChdgG (B:s
(3CNHQfG GdEeGe CHh GdahGQS Hf ShGQ Yf CfS Cf GdfHi Udi dGdg Ydjg hSde CYJb UajI HfJ Mi hLYd YJbgG UOGbJgG s
(3BNQgG (B:s
(3ef MOjK eGYR (B" (3abGe dfG aQejfGg MJi ScJ eeG GSJZaQ dg GdfHi Udi Gddg Ydjg hSde s
(3GdfSNI HgG MhGTs
(3HBNQgG bQGAI SfI (B597 (3hCNQi SfI (B680 (3hYdi GdCUd Gdefbhd efg SeGY SfI (B481 (3hBNQ SfI (B541 s
(3hHChdgG SeGY ddMGaX VjGA GdOjf eMeO Hf YHO GdhGMO GdebOSi hdeMeO Hf YHO GdhGMO GdebOSis
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs